Neutron diffraction studies of Escherichia coli dihydrofolate reductase complexed with methotrexate - Bennett, Brad (National Academy of Sciences, 2006)
Hydrogen atoms play a central role in many biochemical processes yet are difficult to visualize by x-ray crystallography. Spallation neutron sources provide a new arena for protein crystallography with TOF measurements enhancing data collection efficiency and allowing hydrogen atoms to be located in smaller crystals of larger biological macromolecules. Here we report a 2.2-Å resolution neutron structure of Escherichia coli dihydrofolate reductase (DHFR) in complex with methotrexate (MTX). Neutron data were collected on a 0.3-mm(3) D(2)O-soaked crystal at the Los Alamos Neutron Scattering Center. This study provides an example of using spallation neutrons to study protein dynamics, to identify protonation states directly from nuclear density maps, and to analyze solvent structure. Our structure reveals that the occluded loop conformation [monomer (mon.) A] of the DHFR·MTX complex undergoes greater H/D exchange compared with the closed-loop conformer (mon. B), partly because the Met-20 and β(F-G) loops readily exchange in mon. A. The eight-stranded β sheet of both DHFR molecules resists H/D exchange more than the helices and loops. However, the C-terminal strand, βH, in mon. A is almost fully exchanged. Several D(2)Os form hydrogen bonds with exchanged amides. At the active site, the N1 atom of MTX is protonated and thus charged when bound to DHFR. Several D(2)Os are observed at hydrophobic surfaces, including two pockets near the MTX-binding site. A previously unidentified D(2)O hydrogen bonds with the catalytic D27 in mon. B, stabilizing its negative charge.